MODAL VERBS AND INTERLANGUAGE PRAGMATICS: ANALYZING LEARNER DISCOURSE - Abdullayev Shaxobiddin (Journal of new century innovations, 2024)
The acquisition and use of modal verbs in non-native English speakers' discourse represent a significant aspect of interlanguage pragmatics. This article delves into the exploration of how learners of English acquire and utilize modal verbs in their communicative interactions. By examining the challenges and strategies employed by English language learners in mastering modal verbs, this study aims to shed light on the role of interlanguage pragmatics in shaping learner discourse and enhancing language proficiency.